Genetic differentiation, demographic history and distribution models of high alpine endemic vicariants outline the response of species to predicted climate changes in a Central Asian biodiversity hotspot. (November 2022) - Vintsek, Lizaveta; Klichowska, Ewelina; Nowak, Arkadiusz; Nobis, Marcin
Graphical abstract: Highlights: Global warming is the main threat to cold-adapted plants in mountain hotspots. Past climate affects demographic history and current distribution of mountain plants. Geographic vicariants variously respond to forecasted climate changes. S. gracilis and S. zeravshanica are neoendemics originated in the late Pleistocene. Predicted climate warming threatens rocky vegetation in the western Pamir-Alai Mts. Abstract: Understanding species distribution, genetic diversification and evolutionary history is extremely important for mountainous regions with a high diversity of endemic species, which are particularly sensitive to climate change. In this study, we use environmental and molecular data obtained from genome-wide analyses to infer the genetic variability, demographic processes, and response of the cold-adapted, endemic geographical-vicariants Stipa gracilis (distributed in the Tian Shan Mts) and S. zeravshanica (distributed in the western Pamir-Alai Mts) to Quaternary climatic oscillations in a Central Asian mountain biodiversity hotspot. Genomic-based reconstructions of demographic history indicate that the examined endemics presented larger effective population sizes during the Last Glacial Maximum (LGM) period and experienced parallel demographic declines afterward. The results of fastSTRUCTURE analysis revealed three genetic clusters within S. gracilis populations and two within S. zeravshanica . The past distribution models reveals the glacial connectivity of both species, resulting in the detection of an admixture of S. zeravshanica genes in the specimens from the westernmost 'Alaian' population of S. gracilis . Although the occurrence of both species is closely associated with calcareous rocks, the differences in the ranges of the species distributions depend mostly on climatic factors, especially temperature and precipitation. The wider realized ecological niche of S. gracilis allows it to better adapt to global warming and potentially extend its range in the future, while S. zeravshanica, with its narrower niche, is more susceptible to environmental changes and potentially at risk of extinction. The findings will contribute to a better understanding of the factors shaping the distribution and genetic differentiation of mountain endemic species and provide a theoretical basis for their conservation by identifying areas sensitive to climate change in biodiversity hotspots.